2005
DOI: 10.1111/j.1600-051x.2005.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk of gingival overgrowth in patients treated with diltiazem or verapamil

Abstract: Patients taking diltiazem are at high risk for gingival enlargement and gingivitis has a stronger effect than the drug treatment on gingival enlargement risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 30 publications
1
28
0
4
Order By: Relevance
“…However, the causes of GO are complex. In fact, the degree of the GO may differ in the same patient's gingiva by location, probably due to the degree of plaque retention (31)(32). Pathologically, the condition of gingival tissues varies by case, ranging from edematous/strongly inflamed to fibrous/weakly inflamed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the causes of GO are complex. In fact, the degree of the GO may differ in the same patient's gingiva by location, probably due to the degree of plaque retention (31)(32). Pathologically, the condition of gingival tissues varies by case, ranging from edematous/strongly inflamed to fibrous/weakly inflamed.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies that evaluated diltiazem-induced gingival enlargement in humans [4][5][6][7] had to deal with a heterogenous sample regarding age, duration of drug use, dose and other variables. Therefore, further research using animal models should be undertaken to evaluate the behavior of gingival tissue after long-term use of diltiazem, in order to evaluate other mechanisms that might be involved in gingival overgrowth, not only gingival infl ammation.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 On the other hand, there are few reports of diltiazeminduced gingival overgrowth in humans. [4][5][6][7] The fi ndings of a recent study 8 showed that in rats with noninfl amed gingival tissue, diltiazem did not induce gingival overgrowth. Nevertheless, the pathogenesis of drug-induced gingival enlargement is uncertain and confl icting and has been related to several factors, namely age, gender, treatment duration, plasmatic and salivary drug concentration, presence of bacterial biofi lm, gingival tissue infl ammation, genetics and synergism with other medicaments.…”
Section: Introductionmentioning
confidence: 99%
“…Celle-ci peut être soit inflammatoire (locale par une irritation chronique, généralisée par un désordre systémique), soit fibreuse (génétique, médicamenteuse). L'hyperplasie d'origine médicamenteuse est un effet secondaire connu à la prise de plusieurs molécules, notamment de la phénytoïne, la ciclosporine A et la nifédipine [1], un autre antagoniste calcique. Des facteurs favorisants, tels qu'une hygiène bucco-dentaire déficiente ou des facteurs d'irritation locaux (restaurations débordantes, prothèses mal adaptées) sont également décrits [1].…”
Section: Réponseunclassified